Incarcerated inguinal hernia containing urinary bladder and bladder calculi. Issue 1 (24th January 2023) - McLain, Sarah; Cecire, Jack; Mekisic, Allan
Abstract: Inguinoscrotal herniation of the bladder is an uncommon condition. Clinicians should have a high index of suspicion for involvement of the bladder within a hernia when the lower urinary tract urinary symptoms are concurrently present in patients presenting with a painful groin lump. We report the case of a patient who presented with an inguinoscrotal hernia involving the urinary bladder, which was irreducible due to the fact that the herniated portion of the bladder contains multiple containing calculi. The patient underwent successful operative repair of the hernia and had an uncomplicated post-operative course. Key takeaway messages for clinicians are that the presence of lower urinary tract symptoms in a patient concurrently presenting with a groin lump should raise suspicion of bladder involvement within the hernia and that pre-operative imaging is valuable to identify the contents of the hernia to allow safe operative planning and to reduce the risk of bladder injury during surgery.